Carbon dioxide binding to metal oxides: Infrared spectroscopy of NbO2+(CO2)n and TaO2+(CO2)n complexes - Iskra, A; Gentleman, A; Cunningham, E; Mackenzie, S (Elsevier, 2018)
We report the results of an infrared photodissociation spectroscopy study to determine the structures of gas–phase NbO2(CO2)n+ and TaO2(CO2)n+ (n = 1–7) ion–molecule complexes. The experimental spectra, recorded in the region of the CO2 asymmetric stretch using the inert messenger technique, are interpreted in terms of energetically low–lying structures calculated from density functional theory. Together, experiment and simulation provide important new information on CO2–binding relevant to prototypical metal–oxide frameworks. Key findings include strong binding of the first two CO2 ligands to the MO2+ species and clear evidence for a first solvation shell at n = 4. Some features characteristic of a possible CO3 (“carbonate”) moiety are found in spectra for n ≥ 3 but oxalate structures, observed in some similar systems, appear to be too high in energy to be observed experimentally. CO2 activation, reactivity and sequestration have long been of interest to Prof Helmut Schwarz, in whose honour this special issue is published on the occasion of his 75th birthday.